STRATEGIC MANAGEMENT OF THE HIGHER EDUCATION SYSTEM AS AN ECONOMIC DIAGNOSTIC OBJECT - Berdiyev J. Q. (Zeta Repository, 2023)
During the years of independence, a lot of work was done in the higher education system of our country to train qualified specialists in accordance with the requirements of the time. Improving the quality of higher education, organizing the strategic management activities of higher education institutions on the basis of modern requirements, the correct assessment of innovative management activities are especially important in the preparation of qualified personnel in the higher education system. From this point of view, it is very important to conduct scientific research on the process of training competitive personnel in the higher education system, study the theoretical foundations of strategic management, as well as improve the methodological foundations of strategic management activities. The article discusses the features of the strategic management of the higher education system as an object of economic diagnostics. The role of economic diagnostics in ensuring the efficiency of the higher education system and the importance of the principles of diagnostics in strategic management are emphasized. Approaches to assessing the quality of higher education are based on the results expected by subjects interested in the educational process. A scientific conclusion and practical recommendations related to the economic evaluation of the strategic management of the quality of higher education are given.